Ring 18 chromosome associated with cleft palate: case report and comprehensive literature review of clinical symptoms - Matyskova, Dominika; Richtrova, Michaela; Novotna, Alzbeta; Koskova, Olga (Orphanet journal of rare diseases, 2024)
BACKGROUND: Ring 18 chromosome is a rare chromosomal aberration associated with a wide range of symptoms affecting all organ systems. One possible symptom associated with this condition is an orofacial cleft. However, to date, there are very few reported cases where the cleft has been surgically treated. CASE DESCRIPTION: In our case study, we present a female patient with Ring 18 chromosome who underwent cleft palate surgery at 14 months of age. Subsequently, a reoperation of the palate was necessary due to wound dehiscence. For the secondary reconstruction of the palate, the acellular dermal matrix (ADM) MatriDerm® was used to improve healing. The cleft palate surgery progressively improved her ability to take in food, allowing a transition from nasogastric tube feeding to oral intake. RESULTS: This is only the fourth reported case of a child with Ring 18 chromosome undergoing surgical correction of an orofacial cleft. Additionally, it is one of the first cases where an ADM MatriDerm® was used in the surgical correction of a cleft palate. In this study, we also present a comprehensive literature review, providing an overview of the various symptoms associated with this syndrome. CONCLUSION: Cleft palate surgery had a very positive effect on improving food intake in the patient with Ring 18 chromosome. The use of an acellular dermal matrix during the secondary cleft palate surgery led to improved healing and a good outcome.
Keywords: Cleft Palate; Chromosomes, Human, Pair 18; lidé; Female; lidské chromozomy, pár 18; rozštěp patra; Infant; Ring Chromosomes; kojenec; kruhové chromozomy; ženské pohlaví; Humans